Applicability of Vaisburd and Evdokimov Model to Ionic Targets - Sabrin, F.; Uddin, M. A.; Haque, A. K. F. (Journal of Scientific Research, 2012)
The Vaisburd and Evdokimov proposed an empirical model to calculate the electron impact single ionization cross-sections of atoms and molecules. The model has been applied to some atoms and molecules. To examine the efficiency of the model, the present work applies the model to calculate cross-sections for Ne-isonuclear series Ne+, Ne2+, Ne3+, Ne4+, Ne5+, Ne6+, Ne7+, Ne8+, Ne9+ . The separate sets of values of the parameters of the model are determined by comparison with the available experimental data using a non-linear least-squares fitting computer code. Keywords: Electron impact ionization; Empirical model; Ionic targets. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i2.8704 J. Sci. Res. 4 (2), 307-313 (2012)